Pengaruh Pemanfaatan Feromon Seks terhadap Serangga Hama - Edhi Martono (Universitas Gadjah Mada, 1997)
Pheromones are chemical substances used by insects to communicate within their species. Our understanding about pheromones' chemistry, their functions and their overall performances over insect behavior provide us with wealth of information that lead to their use for insect pest control. The use of insect pheromones, particularly sex attractants, is quite advanced, but little information is available about Indonesian indigenous harmful insects' pheromones. More research and investigations need to be done to obtain target-specific substances rather than simply utilize imported products. Their implementation into Integrated Pest Management using farmers-oriented technology should be considered.